Measurement issues associated with conditional reasoning tests: An examination of faking - Bowler, Jennifer L.; Bowler, Mark C.; Cope, John G. (Personality and individual differences, 2013)
•Conditional reasoning tests measure personality by assessing implicit cognitions.•Responses on CR-based measures are typically unaffected by response distortion.•Two studies assessed the fakability of a CR measure of addiction proneness.•Results indicate that the CR measure is resistant to response distortion. Conditional reasoning (CR) is a new item format that measures personality by indirectly assessing reliance upon the cognitive biases associated with specific traits (James et al., 2005). Previous research suggests that, relative to self-report measures, responses on CR-based measures are more difficult to distort (LeBreton, Barksdale, Robin, & James, 2007). The issue of response distortion in the context of CR-based measures was evaluated in two studies. Study 1 (within-subjects) and Study 2 (between-subjects) both investigated whether responses on a CR-based test of addiction could be faked when indirect assessment was upheld. Results of both studies indicated that, unlike a self-report measure of a similar construct, the CR-based measure was unaffected by response distortion.